Effect of Physical and Chemical Parameters on the Activity of Purified Phosphatase Enzyme Produced by Bacillus cereus - N. Danial, Enas; I. Alkhalf, Maha (International Journal of Biotechnology for Wellness Industries, 2018)
Phosphorus is one of the most important nutrients for plant growth and development. This study aimed to survey the optimum condition for phosphatase enzyme production, purified and studied its properties. Phosphatase enzyme activity was determined by end point method. Phosphatase enzyme was obtained from Bacillus cereus EME 66 isolate. The enzyme was purified and characterized, using a three-step purification procedure with 12.3-fold. The phosphatase enzyme was partially purified using ammonium sulfate fractionation followed by ultrafiltration. The acid phosphatase is a monomer protein purified gel filtration to 5.6 fold. Results showed that the optimum temperature for the purified enzyme activity was 60 °C and it was stable at temperatures below 60 °C. This enzyme was stable between pH 4.0-6.0, and the optimal pH activity was found to 5.0. The activity of the enzyme enhanced by heavy metals (Fe3+, Cu2+, Ca2+, Mg2+ and K+). The enzyme activity was strongly inhibited by heavy metals Zn2+. The present article reveals on enzymatic characterization of acid phosphatase enzyme.